Analisis Disparitas Putusan Tindak Pidana Tentang Pengedaran Obat Tanpa Izin Edar - Melinda, Putri (Journal of Comprehensive Science, 2025)
This research discusses the phenomenon of disparity in court decisions against perpetrators of the crime of distributing drugs without a distribution permit in Indonesia. This disparity raises questions about equality and justice in the criminal justice system. This research departs from the differences in verdicts between two cases that have similar offenses, namely Decision Number 27/Pid.Sus/2023/PN Dmk and Decision Number 4/Pid.Sus/2023/PN Kln. Both cases involved offenders who distributed hard drugs without a distribution permit, but received significantly different criminal sentences. This study aims to determine the consideration of judges in imposing unequal criminal verdicts and what factors are the causes of the criminal act of distributing drugs without a distribution permit. Through a normative juridical approach, this study found that the main factors of disparity stemmed from the judges' interpretation of the severity of the offense, the amount of drugs distributed, and the social and economic conditions of the defendant. In one case, the defendant was sentenced to a heavier penalty because he was deemed to have earned more profit and circulated large quantities, while in another case, the defendant only received a lenient sanction because of small-scale circulation. This disparity reflects the lack of clear guidelines in sentencing and opens room for subjectivity in the judicial process. The theoretical basis used is Law Number 36 of 2009 as well as Decision Number 27/Pid.Sus/2023/PN Dmk and Decision Number 4/Pid.Sus/2023/PN Kln.The research confirms the need for harmonization in criminal decisions to reduce inequality and increase public confidence in the justice system. The proposed recommendation is the establishment of a more structured standard for judges in deciding cases related to the distribution of drugs without a distribution permit, in order to create more consistent and transparent justice.